Experimental investigation on the characteristics of temporary cavity in BABT with 9 mm projectiles. (June 2021) - Luo, Shaomin; Wen, Yaoke; Li, Juan
Abstract: Temporary cavity, one physical phenomenon in BABT reflects the dynamic response of biological tissues and is used to evaluate the trauma. To clarify the characteristics of cavity evolution during 9 mm Luger penetration, we obtain the deformation profiles by using an experimental method with a high-speed camera and thereby visualize the cavity formation and development. According to the dynamic impact experiments at the velocity from 220 to 420 m/s, the temporary cavity profile can be approximately regarded as a semi-ellipsoid. The maximum depth increases as a quadratic function of velocity. Additionally, the maximum volume of the temporary cavity is attained significantly after the maximum depth. The change rate of cavity volume in the expansion stage is larger than that in the contraction stage. Highlights: Analysis of behind armor blunt trauma. Study of cavity evolution. Changes of cavity volume and the maximum depth. Influences of velocity on cavity forming.